Bioactive LbL-assembled multilayer nanofilms upregulate tenogenesis and angiogenesis enabling robust healing of degenerative rotator cuff tendons in vivo. (23rd August 2019) - Han, Fei; Zhang, Peng; Wen, Xuejun; Lin, Chao; Zhao, Peng
Abstract : The aim of this work was to fabricate LbL-assembled multilayer film-modified aligned scaffolds and investigate their regulation of TSPCs and potential for degenerative tendon healing. Abstract : Degenerative changes to rotator cuff tendons are often diagnosed in elderly patients. Spontaneous healing of degenerative tendons is rather inefficient as a result of the lack of a suitable microenvironment for tendon stem cell differentiation and vascularization. Herein, multilayer hyaluronic acid/chitosan (HA/CS) nanofilms were assembled by a layer-by-layer assembly method onto aligned poly(ε-caprolactone) (PCL) nanofibers for use in healing degenerative tendons. Materials testing showed that the number of layers of HA/CS nanofilms could adjust the hydrophilicity and wettability of the nanofibrous membranes. In vitro, the optimal 8-layer (termed as 8LP) membrane afforded aligned morphology of tendon stem/progenitor cells (TSPCs) and up-regulated mRNA expression of tenogenic markers (SCX, BGN). In a rabbit model with disorganized rotator cuff tendons, the 8LP group up-regulated mRNA levels of collagen I/III and tenascin (TNC) at 6 weeks, but not 12 weeks, post-surgery as compared to the native PCL group. Next, vascular endothelial growth factor-loaded 8LP (termed as 8LP-V) was prepared. Compared to 8LP, 8LP-V produced higher levels of angiogenesis in the tendons at 6 or 12 weeks post-surgery, thus supplying endogenous pre-tendon growth factors (TGF-β, IGF-1) to further enhance tenogenic transcriptional factors. As a result, 8LP-V yielded thicker collagen fibers and/or higher tendon stiffness as compared to the 8LP and clinical pericardial patch groups. This study highlights the rational design of LbL-assembled multilayer HA/CS films to upregulate tenogenesis for robust healing of degenerative rotator cuff tendons.